Identification of the Parent Activity in helping the development of social skills – Emotional children ages 5-6 Years in Kindergarten Independent Islamic, Percut Sei Tuan, Medan Deli Serdang Regency. TA. 2018-2019 - Nur Dwi Febrianti; Anita Yus; Yusnadi Yusnadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This event will be based on research to find out the parent activity in helping develop social-emotional ketermpilan ages of 5-6 years in the accompanying children,  establish good communication with the child, give a chance in children, keep an eye on children in order to remain controlled, encouragement or motivation of the child, redirect the child to have and develop the basics of self discipline. This research aims to know the social-emotional skills development of children ages 5-6 years in Islamic kindergarten independent sub-district of percut sei tuan deli serdang district ta.  2018 – 2019 and to know activities performed parents in cleaner development of social skills-emotional children aged 5-6 years in Islamic kindergarten independent sub-district of percut sei tuan deli serdang district ta. 2018-2019. The methods used are qualitative research methods. The data source that is taken is the father who served as head of the household and the mother who served as housewives in a kindergarten independent Islamic as much as 5 (five) head of the family that serves as the source of the informant. The results showed that there is a difference between the children who accompanied the same parents with children who are not accompanied by her parents in helping the development of the social-emotional skills of children aged 5-6 years in kindergarten independent Islamic with children who are not accompanied by her parents in helping the development of the social-emotional skills of children aged 5-6 years in kindergarten independent Islamic in associating with other people by way of doing activities together with teachers and classmates, follow instructions with how to accomplish the task as instructed, to identify and manage those emotions and behavior in a manner express themselves in accordance with the emotional conditions indicated, thinking of the right solution to conflict with how to determine the right way if you're having difficulty, hang on to the task by means of the task given to the penyele saian, and engage in social conversations and cooperative play by taking the initiative to invite friends to talk.